2018
DOI: 10.1259/bjr.20170707
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of combining conventional, diffusion-weighted imaging and dynamic contrast-enhanced MRI for salivary gland tumors

Abstract: An evaluation combining MRI morphologic findings and functional MRI (ADCs and TIC) appears to be useful in differentiating benign from malignant tumors in salivary gland tumors. Advances in knowledge: The study firstly dealt with the combination of conventional MRI, DWI-MRI with DCE-MRI in salivary gland tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 22 publications
(25 reference statements)
2
39
0
1
Order By: Relevance
“…Analysis of TIC had high sensitivity and specificity in differentiating benign from malignant parotid gland tumors. Pleomorphic adenoma could be easily Zheng et al [7] evaluated salivary gland tumors based on the TIC classification by Yabuuchi et al [6] and found that most cases of pleomorphic adenomas (88.9%) had type A TIC; all cases of Warthin's tumor had type B TIC; regarding malignant parotid gland tumors, most of them (81.8%) had type C TIC, and only 18.2% had type B TIC. Lam et al [8] also studied TIC in differentiation between benign and malignant parotid gland tumors and found that 96.2% of pleomorphic adenomas had type A TIC; type C TIC was observed in all cases of malignant parotid gland tumors except lymphoma.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of TIC had high sensitivity and specificity in differentiating benign from malignant parotid gland tumors. Pleomorphic adenoma could be easily Zheng et al [7] evaluated salivary gland tumors based on the TIC classification by Yabuuchi et al [6] and found that most cases of pleomorphic adenomas (88.9%) had type A TIC; all cases of Warthin's tumor had type B TIC; regarding malignant parotid gland tumors, most of them (81.8%) had type C TIC, and only 18.2% had type B TIC. Lam et al [8] also studied TIC in differentiation between benign and malignant parotid gland tumors and found that 96.2% of pleomorphic adenomas had type A TIC; type C TIC was observed in all cases of malignant parotid gland tumors except lymphoma.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
“…Regarding WR values of Warthin's tumor and malignant parotid gland tumor, Zheng et al [7] stated that WR of Warthin's tumor (57.5 ± 8.1%) was significantly higher than that of malignant parotid gland tumors (17.2 ± 13.2%). Gokce [5] performed analysis of several previous studies in literature and concluded that WR value of Warthin's tumor was significantly higher than that of malignant parotid gland tumors.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the ADC values of salivary gland tumors, Terra et al 10 showed that the mean ADC values for pleomorphic adenoma was 1.91 × 10 −3 mm 2 s −1 . Zeng et al 17 showed that the mean ADC values for the different mass types were as follows: 1.72 × 10 −3 mm 2 s −1 for pleomorphic adenomas, 0.74 × 10 −3 mm 2 s −1 for adenolymphoma, and 0.95 × 10 −3 mm 2 s −1 for malignant tumors. In this study, ADC values of minor salivary gland tumors were adenoid cystic carcinoma: 0.86 × 10 −3 mm 2 s −1 , pleomorphic adenoma: 1.49 × 10 −3 mm 2 s −1 , and myoepithelioma: 1.71 × 10 −3 mm 2 s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Eine Studie von Aghaghazvini et al zeigte, dass mittels DCE-Sequenz eine Differenzierung der Tumorentität bei Speicheldrüsentumoren vereinfacht werden kann[17]. Auch die Studie von Zheng et al demonstrierte, dass die DWI-wie auch die DCE-Sequenz nützliche Informationen bezüglich der Einordnung von Tumoren der Speicheldrüse liefert[18]. Ähnliche Ergebnisse liefern auch andere Studien, die die Effektivität der DWI-bzw.…”
unclassified